Interdicto de obra nueva. Medidas de no innovar. Habilitación de día y hora. - Ballestero Barruti, Ricardo D. J. (Lecciones y Ensayos, 2025)
Interdicto de obra nueva. Medidas de no innovar. Habilitación de día y hora.